Hubungan Regulasi Emosi dengan Hasil Belajar Siswa SMP Negeri 11 Padang - Sari, Putri Ayu Debie Mustika; Pratiwi, Dita; Ulhaq, Qanita Aulya; Zai, Surya Intan Putri; Tashma, Clarissa Maharani; Hidayati, Izzanil (YASIN, 2024)
The purpose of this research is to find out the learning outcomes of SMP Negeri 11 Padang students are related to emotional regulation, because student learning achievement decreases as a result of a lack of emotional regulation. One of the methods used in this research is quantitative method. The population in this study were grade VII students at SMP Negeri 11 Padang, which had 238 students. The research sample itself consisted of 149 people, who were then randomly divided into seven classes. To collect data in this study, the researcher used a Likert scale questionnaire. This study used product moment correlation test to analyze the data. The results showed that emotional regulation of 67.8% of students in SMP Negeri 11 Padang was moderate, with a correlation coefficient of 0.231 and a significance value of 0.005. This shows a very positive relationship between emotion regulation and student learning outcomes.